Preparing Advanced Clinicians and Practitioners: A Model for Mentorship in Occupational Therapy Practice - Sarah A. Schoen; Bryan M. Gee; Mim Ochsenbein (Hindawi-Wiley, 2021)
Mentoring is essential at all stages of a professional career. However, little has been written about the effectiveness of programs for practicing clinicians. This study was designed to address the need for evidence about the effectiveness of formal mentorship programs by describing the impact of the STAR mentorship program on a group of clinicians specializing in sensory integration and processing challenges. This study utilized an exploratory, retrospective, survey research design. Course evaluations were examined from 240 subjects following participation in a one-week, small group mentorship training program. Qualitative methods were adapted for use in this study. Sixteen codes, with operational definitions, were developed to analyze the surveys. Ninety-six percent indicated that the program met or exceeded their expectations; only 12.5% had a negative comment. Impact on psychosocial function was reflected by 22% of the participants. Comments related to impact on career function were indicated by 45% of the participants. Ninety-four percent provided positive comments about the program structure, and 74% responded with positive comments regarding content of the program. Positive outcomes were associated with this one mentorship program, suggesting a need for more in-person, structured mentored learning experiences. Mentorship is recommended as a method to address the growing need within the profession to support career development, build knowledge, skill and attitudes, and aspirations/commitment as well as enhance professionalism/professional development.